STUDY OF TECHNICAL AND LEVEL OF THE ENVIRONMENTAL FRIENDLY OF THE COASTAL LIFTNET (KELONG PANTAI) IN TANJUNG UMA VILLAGE, OF SUB DISTRICT LUBUK BAJA BATAM CITY, RIAU ISLANDS PROVINCE - Marpaung, Marudut; Bustari, Bustari; Sari, T. Ersti Yulika (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted in December 2017 in Tanjung Uma Village, Lubuk Baja Sub District, Batam City, Riau Islands Province. This study aims to identify the technique of identify the liftnet fishery technique at coastal area (kelong pantai), and to know the level of environmental friendliness that is under taken by interview the stake holder by using the questionare and the number of respondens are 20 people. The operation of the coastal liftnet (kelongpantai) activity done in the afternoon, or depending on the tides. The nets material of coastal lifnet is made of green polyetilene (PE) multifilament material.With 1,5-2,5 inchi os mesh size. The nets measure for making the nets of coastal liftnet is ±235 meters.Based on the analysis of environmental friendliness level of FAO 1995, the percepcion of the respondents result the value obtained is 24,5, which mean this gear can classitied in environmentally friendly gear by FAO 1995. Keyword: contribution of environmental parameters, simple regression analysis, purse seine.